Romania's development to a low-tax country: Effective corporate tax burden in Romania from 1992 to 2010 and Romania's current ranking among the eastern European member states - Christoph Spengel; Sebastian Lazar; Lisa Evers; Benedikt Zinn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We trace back Romania's development to a low-tax country among the Member States of the European Union by analysing the major tax law changes in corporate taxation since 1992. We find that the significant reduction of the corporate income tax rate from 45% in 1992 to 16% since 2005 has not been accompanied by a comprehensive broadening of the corporate income tax base as prevalent in many longstanding Member States of the EU and the OECD. Our analysis is not limited to a comprehensive description of the development of corporate taxation in Romania, but goes on with a numerical analysis of the tax burdens at different periods of time which constitute milestones in the development of corporate taxation in Romania. For this purpose, we apply the European Tax Analyzer, which is a computer-based model firm approach. We find that the average company tax burden of the underlying model company has dropped significantly by almost 65% since 1992. Furthermore, our numerical analysis does not confirm the tax base broadening policy. As a result, Romania holds position two among the group of Central and Eastern European EU Member States.
Keywords: H22; H25; O38; 330; corporate taxation; effective tax burden; transition economy; EU accession countries; tax reform; tax-rate-cum-base-broadening reform; Unternehmensbesteuerung; Steuerreform; Steuerwirkung; Steuerbelastung; Übergangswirtschaft; EU-Erweiterung; Rumänien